Shark fossil diversity (Squalomorphii, Squatinomorphii, and Galeomorphii) from the Langhian of Brielas (Lower Tagus Basin, Portugal) - Fialho, Pedro R. (2021)
The fossiliferous marine Miocene sediments of the Lower Tagus Basin (Portugal) present a great diversity of Chondrichthyes forms. The current study focuses on the fossil sharks from the Langhian Vc unit of the Brielas section, located in the Setúbal Peninsula. A total of 384 isolated fossil teeth were analysed and ascribed to 17 species from the Orders Hexanchiformes, Squaliformes, Squatiniformes, Lamniformes, and Carcharhiniformes. Centrophorus granulosus and Iago angustidens are described for the first time in Portuguese sediments, whereas Pachyscyllium dachiardii and Rhizoprionodon ficheuri represent only their second reported occurrence. Galeorhinus goncalvesi was already known from the Portuguese uppermost Miocene (Alvalade Basin), but it is now recognized in older sediments. Furthermore, the new material seems to include the first reported occurrence of Hexanchus cf. agassizi in Miocene sediments. As a whole, these new findings support the previous palaeoenvironment characterization of a warm infralittoral setting gradually deepening to a circalittoral one, where seasonal upwelling phenomena could have occurred.